2015
DOI: 10.5653/cerm.2015.42.4.131
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction and subfertility

Abstract: The thyroid hormones act on nearly every cell in the body. Moreover, the thyroid gland continuously interacts with the ovaries, and the thyroid hormones are involved in almost all phases of reproduction. Thyroid dysfunctions are relatively common among women of reproductive age, and can affect fertility in various ways, resulting in anovulatory cycles, high prolactin levels, and sex hormone imbalances. Undiagnosed and untreated thyroid disease can be a cause of subfertility. Subclinical hypothyroidism (SCH), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
0
26
0
2
Order By: Relevance
“…As case 1 had a smaller r (X) chromosome compared to case 2, we analysed the additional genes deleted and found that the extra region deleted in case 1 (Xq21.33-Xq22.1) were harbouring genes involved in thyroid hormone signalling, insulin receptor signalling, meiosis regulation, cell cycle regulation and chromatin organization. Alterations in these pathways are reported to be responsible for ovarian dysfunction [1,5,9,31,36,46].…”
Section: Discussionmentioning
confidence: 99%
“…As case 1 had a smaller r (X) chromosome compared to case 2, we analysed the additional genes deleted and found that the extra region deleted in case 1 (Xq21.33-Xq22.1) were harbouring genes involved in thyroid hormone signalling, insulin receptor signalling, meiosis regulation, cell cycle regulation and chromatin organization. Alterations in these pathways are reported to be responsible for ovarian dysfunction [1,5,9,31,36,46].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SCH in sub fertile women has been reported to vary from 0.7% to 43%. 9 History of infertility was there in 20.4% of present study population. Among them Subclinical hypo and hyperthyroidism was observed to an extent of 28% in each group.…”
Section: Resultsmentioning
confidence: 72%
“…For our patient, the time from adopting a gluten-free diet to delivery of a baby was 17 months. Infertility is also associated with thyroid autoimmunity (14), and increased prevalence of hypothyroidism among women with celiac disease have been reported (15). Co-existent autoimmune thyroid disease and celiac disease may be due to a common genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%